The trans-boundary activities and the security level along the Sarawak and West Kalimantan Border/ Mohd Salehuddin Mohd Salleh, Faisal Othman & Zaaba Zulkifli - Mohd Salleh, Mohd Salehuddin; Othman, Faisal; Zulkifli, Zaaba
This study is carried out to explain the issues of security level at theborder of Tebedu, Sarawak and West Kalimantan. This area is a popular place for trans-border market that existed for many generations. The Tebedu - Entikong crossing was declared and upgraded to an international overland trade- crossing route in 1995. These two countries are separated by a mountainous landmass thus naturally giving it a strategic area to encourage illegal immigration and illegal cross border activities that lead to security threat to Malaysia. This study attempts to seek for the types of illegal activities, the people that involved in the activities, the mode of transportation and the people awareness regarding of these activities.